MULTILATERAL SAFETY IN NORTHEAST ASIA AND ROLE OF KOREA (International relations and international law Journal, 2016)
North-East Asia is attracting more and more attention of theinternational community. However, the fact that in this huge areawith great economic and political infl uence, there is no leadingregional security organization, remains cause for more concernsfor the international community. If a situation is like this, whatthe new order will be applied to replace the world order duringthe “Cold War”? We see that in the modern international community,the mainstream of world politics is to ensure peace andstability in international relations on the basis of multilateral cooperation.NEA also can not be an exception. It’s clear that afurther strengthening of economic cooperation and a multilateralsystem of cooperation in security area completely in the interestsnot only for each country but also for the region and the world. Tocreate a multilateral security in Northeast Asia to respond to varioussecurity issues in the region, primarily to establish mutualtrust and then on the basis of this trust to continuously expand thescope of cooperation and fi nally to create a multilateral securitysystem. In particular, the existing six-party talks to resolve NorthKorean nuclear problem may be the most ideal way to fulfi ll thisrole. Many experts highly evaluated the possible role of these negotiations,particularly with regard to nuclear non-proliferationand security cooperation in Northeast Asia. The role of SouthKorea, which gradually became the center of NEA and the worldis certainly very important. South Korea as a “bridge” must be amediator for the stabilization and regional security.
Keywords: multilateral safety; Northeast Asia